24 Cardiac arrest patients presenting to hospitals at weekends are not subject to the weekend effect: insights from the ACALM big data, united kingdom. (May 2019) - Potluri, Rahul; More, Ranjit; Chalil, Shajil; Patel, Billal; Ainslie, Mark; Chandran, Suresh
Abstract : Introduction: Patients presenting to hospital with a cardiac arrest are associated with significant mortality in the United Kingdom. There is widely debated evidence to support a ''weekend-effect'' with mortality rates elevated for patients admitted to hospital on the weekend. However, cardiac arrest teams are on call in every acute hospital 24 hours a day, all year round and the evidence for the weekend affect involving cardiac arrests is unclear. Purpose: To investigate the impact of weekend admission on patients presenting with a cardiac arrest to hospital on mortality utilising ACALM big data. Methods: Anonymous information on patients presenting to hospital with a cardiac arrest was obtained from several hospitals in England, UK between 1st January 2000 and 30th June 2014. This data was processed and analysed according to the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol. ICD-10 and OPCS-4 codes were used to trace patients coded for cardiac arrest, day of admission, patient demographics, prevalence of co-morbidities and mortality data. Kaplan-Meier survival curves and cox regression analyses adjusted for age, gender, ethnicity, Charlson comorbidity index and the top ten contributors to mortality in the UK (Ischaemic Heart Disease, Heart Failure, Bowel cancer, Breast cancer, Lung cancer, Pneumonia, Cerebrovascular disease, Chronic Obstructive Pulmonary Disease and Dementia). Results: There were 4803 patients who presented with cardiac arrest with the majority, 81% of patients were admitted on weekdays. Demographics, co-morbidities and mortality for patients admitted on weekdays and weekends are shown in table 1. Figure 1 shows the Kaplan-Meier survival curve for patients discharged according to weekday/weekend discharge. Cox regression model including age, gender, ethnic group, Charlson comorbidity index and the top ten causes of death in the UK showed that weekend presentation did not contribute to increased mortality (OR 1.01;95%C.I 0.94–1.11;p=0.692) Conclusion: We have demonstrated that the weekend effect is not shown in patients presenting to hospital with cardiac arrests. Our findings can perhaps be explained by the presence of 24/7 cardiac arrest teams present in acute hospitals. Conflict of Interest: Nil